Share Trading in Limited Liability Companies According to the 2007 Law and Fatwa No. 40/DSN-MUI/X/2003 - Muhammad Irkham Firdaus; Theo Aditya Pradhana (Al-Muamalat: Journal of Islamic Economics Law, 2025)
ENGLISH A Limited Liability Company (Perseroan Terbatas/PT) is a legal entity whose assets are separate from the personal wealth of its shareholders, thereby limiting the shareholders' liability to the amount of shares they own. The share instrument in a PT functions not only as proof of ownership but also as an object of trading regulated by specific legal provisions. This research aims to analyze and compare the regulations regarding the practice of share trading in a PT, particularly concerning pre-emptive rights (hak preferensi), as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies, with the Sharia law perspective contained in the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number 40/DSN-MUI/X/2003 on the Capital Market and General Guidelines for the Application of Sharia Principles in the Capital Market Sector. The research method employed is normative-comparative, which involves reviewing and comparing statutory regulations (the PT Law) with Sharia edicts (the DSN-MUI Fatwa). The findings indicate that Article 58 paragraph (1) of the PT Law regulates the pre-emptive rights of other shareholders when shares are transferred, a provision aimed at protecting the ownership structure. Although the DSN-MUI Fatwa focuses on the principles of permissible share transactions free from gharar (uncertainty) and maisir (gambling), no substantive conflict was found regarding the mechanism of share trading, provided that the transaction object (the shares) meets the Sharia criteria. The main difference lies in the philosophical foundation, where the PT Law focuses on legal and corporate protection, while the DSN-MUI Fatwa emphasizes compliance with Islamic muamalah (transactional) principles. This research contributes to the harmonization of corporate regulation in Indonesia with Sharia economic principles. INDONESIA Perseroan Terbatas (PT) merupakan badan hukum yang memiliki kekayaan terpisah dari kekayaan para pemegang sahamnya, sehingga tanggung jawab pemegang saham hanya terbatas pada jumlah saham yang dimiliki. Instrumen saham dalam PT tidak hanya berfungsi sebagai bukti kepemilikan, tetapi juga menjadi objek jual beli yang diatur secara spesifik. Penelitian ini bertujuan untuk menganalisis dan membandingkan ketentuan mengenai praktik jual beli saham PT, khususnya terkait dengan hak preferensi, sebagaimana diatur dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas dengan perspektif hukum syariah yang tertuang dalam Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) Nomor 40/DSN-MUI/X/2003 tentang Pasar Modal dan Pedoman Umum Penerapan Prinsip Syariah di Bidang Pasar Modal. Metode penelitian yang digunakan adalah normatif-komparatif, yaitu mengkaji dan membandingkan peraturan perundang-undangan (UU PT) dengan fatwa syariah (Fatwa DSN-MUI). Hasil penelitian menunjukkan bahwa UU PT Pasal 58 ayat (1) mengatur hak preferensi bagi pemegang saham lain ketika terjadi pemindahtanganan saham, sebuah ketentuan yang bertujuan melindungi struktur kepemilikan. Meskipun Fatwa DSN-MUI fokus pada prinsip-prinsip transaksi saham yang halal dan bebas dari gharar (ketidakjelasan) dan maisir (judi), tidak ditemukan konflik substantif terkait mekanisme jual beli saham, asalkan objek transaksi (saham) tersebut telah memenuhi kriteria syariah. Perbedaan utama terletak pada landasan filosofis, di mana UU PT berfokus pada perlindungan hukum dan korporasi, sementara Fatwa DSN-MUI menekankan kepatuhan terhadap prinsip muamalah Islam. Penelitian ini memberikan kontribusi dalam harmonisasi regulasi korporasi di Indonesia dengan prinsip-prinsip ekonomi syariah.